2010
DOI: 10.1002/jor.21055
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of microRNA (miRNA) in chordoma reveals a role for miRNA‐1 in Met expression

Abstract: Emerging evidence suggests that microRNA (miRNA) expression signatures in cancer may have important diagnostic, prognostic, and therapeutic value, but there is no data on miRNA expression in chordoma. The purpose of this study was to identify the role of miRNAs in human chordoma. We analyzed miRNA expression in chordoma-derived cell lines and chordoma tissue by using miRNA microarray technology with unsupervised hierarchical clustering analysis. The relative expression levels of these miRNAs were confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 25 publications
(32 reference statements)
5
82
1
2
Order By: Relevance
“…[15][16][17]21,23,[42][43][44] More recently, several small non-coding microRNAs, including miR-34b, miR-34c, miR-199a*, miRNA-1, and miRNA-206, have been proved to upregulate MET protein expression in a variety of cancers by either targeting MET mRNA for degradation or repressing its translation post-transcriptionally. 43,[45][46][47] These microRNAs may constitute a novel and critical mechanistic basis to modulate MET expression in tumor cells. Through binding of activated HGF to its extracellular domain, MET undergoes oligomerization with subsequent phosphorylation of multiple tyrosine residues at the intracellular domains of the b subunit, thereby modulating its internalization, catalytic activity, and docking of adaptor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]21,23,[42][43][44] More recently, several small non-coding microRNAs, including miR-34b, miR-34c, miR-199a*, miRNA-1, and miRNA-206, have been proved to upregulate MET protein expression in a variety of cancers by either targeting MET mRNA for degradation or repressing its translation post-transcriptionally. 43,[45][46][47] These microRNAs may constitute a novel and critical mechanistic basis to modulate MET expression in tumor cells. Through binding of activated HGF to its extracellular domain, MET undergoes oligomerization with subsequent phosphorylation of multiple tyrosine residues at the intracellular domains of the b subunit, thereby modulating its internalization, catalytic activity, and docking of adaptor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…downregulated and upregulated myomiRs respectively, and Table 6 lists validated myomiR targets related to enhanced cancer progression. An excellent review by Nohata et al [84] (2012) reported changes in the expression of the miR1/ 133a and miR206/133b cistron clusters in numerous cancers, typically finding reduced expression of different combinations of myomiRs, such as in lung cancer [85] , colorectal cancer [86,87] , rhabdomyosarcoma [88,89] , chordoma [90] osteosarcoma [91] , muscleinvasive bladder cancer [92] , bladder cancer (transitional cell carcinoma) (TCC) [93] , ESCC [94] , breast cancer [95] and prostate cancer [9597] . In different cancers (Figure 3) deregulation typically involves downregulation of one or more myomiR isomers, indicating they normally function as tumor suppressors in the tissues, limiting Metastatic CRC [301] Notch3, Hes1, Bcl-2 and MMP-9; Exogenous upregulation of miR-206 expression;…”
Section: Myomirs and Cancermentioning
confidence: 99%
“…Dysregulation of miRNAs that target the expression of oncogenes or tumor suppressor genes may therefore influence a number of essential biological functions, including cancer initiation and progression (6,7). The role of miRNAs in chordoma has been studied when compared with muscle tissue or adult nucleus pulposus tissues (8)(9)(10). Certain miRNAs are differentially expressed in chordoma and, in particular, miR-1 and miR-31 may have a functional impact on chordoma tumor pathogenesis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The role of miRNAs in chordoma has been studied when compared with muscle tissue or adult nucleus pulposus tissues (8)(9)(10). Certain miRNAs are differentially expressed in chordoma and, in particular, miR-1 and miR-31 may have a functional impact on chordoma tumor pathogenesis (8,9). Nevertheless, the unique expression profiles of miRNAs and their downstream signaling pathways in chordoma remain incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%